Impact of Cordyline fruticosa leaf meal supplemented diet on growth performance, egg production, egg quality, and some heamatological indices of laying hen - Alagbe, John Olujimi (Brazilian Journal of Science, 2024)
At Sumitra Research Institute in Gujarat, India, research was carried out to ascertain the impact of Cordyline fruticosa on the growth performance, egg quality, production, and some heamatological indices of laying hens. 500 – 35 weeks Lohmann brown birds with an initial weight of 1717 grams were randomly distributed into five treatments with five replicates (20 hens per replicate). The basal diet was formulated according to the requirements of the birds. Hens in treatment 1 (control group) were fed basal diet only. The other experimental groups were fed the same diet with the addition of C. fruticosa meal at 10, 20, 30, and 40 g respectively in treatments 2, 3, 4, and 5. Birds were given free access to feed and clean water and a completely randomized design was adopted throughout the 90-day experimental period. Results showed that average weight gains and average daily feed intake followed a similar trend, birds fed C. fruticosa meal had higher body weight compared to the control in this order treatment 5 (T5) (1270.0 g), 4 (1263.0 g), 3 (1233.6 g), 2 (1230.0 g) and 1 (983.1 g) (p < 0.05) respectively. The treatment influenced the average daily feed intake, feed conversion, and mortality rate (p < 0.05). Hen day egg production and hen house egg production were higher in T5 (72.98%, 65.90%), T4 (72.72%, 69.85%), T3 (72.88%, 69.83%), intermediate in T2 (60.09%, 51.00%) and lower in T1 (51.19%, 41.85%). Eggshell strength, eggshell thickness, egg weight, albumen weight, yolk weight, yolk index, and haugh unit were significantly (p < 0.05) different among the treatments. Pack cell volume, haemoglobin, red blood cell, white blood cell, heterophil, and lymphocyte count were influenced by the treatment. However, values fall within the established range for healthy laying hen. It was concluded that Cordyline fruticosa meal can be fed to laying hens up to 40 g kg-1 diet without having any negative effect on their performance and health status.